The phenomenon of social loafing in high school students - Gustiani, Hesti; Yeni, Frischa Meivilona; Neviyarni, Neviyarni; Febriani, Rahmi Dwi; Zahri, Triave Nuzila (International Journal of Applied Counseling and Social Sciences, 2025)
Adolescents tend to join social groups based on similarities and comfort. In group learning, all members are expected to participate equally; however, this is not always the case. Individuals often exert less effort in groups compared to working independently, a phenomenon known as social loafing. This study aimed to describe students' social loafing based on two dimensions: dillution effect and immediacy gap. Using a quantitative descriptive method, the study involved 216 high school students selected through proportional random sampling from a population of 440 students. Data were collected using a validated social loafing scale. Results indicated that social loafing based on the dillution effect dimension was categorized as low (48.15%), while social loafing based on the immediacy gap dimension was categorized as medium (54.63%). School counselor are encouraged to mitigate social loafing through information services, individual counseling, and group counseling interventions.